The Effect of Monetary Policy on Unemployment Rate in Indonesia - Mahadika, Hafiansyah; Wibowo, Wisnu (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2021)
This study aims to determine the influence of monetary policy on the unemployment rate in Indonesia. Unemployment is one of the fundamental problems in the economy. The unemployment problem can be overcome by monetary policy. This study used time series data with the period 1975-2016 using real money demand, economic growth, real interest rates, and real exchange rates as independent variables, and the unemployment rate as the dependent variable. The data used in this study is secondary data obtained from the World Bank. The method used is ARDL (Autoregressive Distributed Lag) which can change a static economic theory to be dynamic by taking into account the role of time explicitly. The results show that in the long run the probability value of the economic growth variable is below the 5% significance level which indicates that economic growth had a negative and significant effect on the unemployment rate. In the short run, the real interest rate, the real interest rate at lag 1, economic growth at lag 1 and lag 3, and the real exchange rate at lag 1 had a negative and significant effect on the unemployment rate. This indicates that the impact of monetary policy on the unemployment rate is temporary.Keywords: Unemployment Rate, Monetary Policy, ARDL.JEL : E24, E52, E61.